Sinergi antar Stakeholder dalam Program Sekolah Ramah Anak Tingkat PAUD di Kota Surabaya (Studi Pada PAUD Percontohan Tunas Asri Kota Surabaya). - Saraswati, I Gusti Ayu Nadya Annas (Jurnal Administrasi Publik, 2016)
Abstract: The Synergy between the stakeholders for implementation of child-friendly school programs in early childhood level in the city of Surabaya (A Study in Early Childhood Pilot Tunas Asri Surabaya). This study is based on the problem the synergy between the stakeholder for implementation of the child-friendly schools program in early childhood level in the city of Surabaya. This study aims to address these problems the  stakeholders and the role of the stakeholders, the synergy between the stakeholders in the implementation of child-friendly school programs in early childhood level in the city of Surabaya and also the supporting and inhibiting factors of synergy between the stakeholders. The synergy that exists between the stakeholders through the principles of child-friendly schools are inclusive education principles, democratic participation and child centered applied through several existing programs in early childhood Pilot Tunas Asri can be implemented by means of coordination and effective communication.   Keywords: synergy, stakeholder, child-friendly school   Abstrak: Sinergi antar Stakeholder dalam Program Sekolah Ramah Anak Tingkat PAUD di Kota Surabaya (Studi Pada PAUD Percontohan Tunas Asri Kota Surabaya). Penelitian ini didasarkan pada permasalahan sinergi para aktor pada  pelaksanaan program sekolah ramah anak tingkat PAUD di Kota Surabaya. Penelitian ini bertujuan untuk menjawab permasalahan siapa saja stakeholder serta peran stakeholder, sinergi antar stakeholder dalam pelaksanaan program sekolah ramah anak tingkat PAUD di kota Surabaya dan faktor pendukung juga penghambat dari sinergi antar stakeholder tersebut. Sinergi yang terjalin antar stakeholder yang ada melalui prinsip sekolah ramah anak yaitu prinsip inclusive education, democratic participation dan child centered yang diaplikasikan melalui beberapa program yang ada di PAUD Percontohan Tunas Asri dapat dilaksanakan dengan cara koordinasi dan komunikasi yang dibangun efektif.   Kata kunci: sinergi, stakeholder, sekolah ramah anak